Chloroquine Inhibits Stemness of Esophageal Squamous Cell Carcinoma Cells Through Targeting CXCR4-STAT3 Pathway - Yue, Dongli; Zhang, Daiqun; Shi, Xiaojuan; Liu, Shasha; Li, Anqi; Wang, Dong; Qin, Guohui; Ping, Yu; Qiao, Yamin; Chen, Xinfeng; Wang, Feng; Chen, Renyin; et al. (Frontiers in Oncology, 2020)
Esophageal squamous cell carcinoma (ESCC) is one of the most prevalent cancers worldwide. Recent studies have shown that cancer stem cells (CSCs) are present in ESCC, are thought to lead to aggressive tumor behavior and the prognosis. The CXC chemokine receptor 4 (CXCR4), is regarded as a putative CSCs marker in various malignancies. Here, we demonstrate that CXCR4 played a key role in ESCC progression and CXCR4 positive ESCC cells possessed stem-like properties. Furthermore, the anti-malarial agent chloroquine (CQ) targeted CXCR4-positive ESCC cells via STAT3 pathway. Therefore, CQ with anti-CSCs effects may be an effective adjunct to current ESCC chemotherapy regimens.